2022
DOI: 10.1021/acs.jmedchem.2c01003
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent Cholinesterase Inhibition-Based Multi-Target-Directed Lead Compounds for Synaptoprotection in Alzheimer’s Disease

Abstract: Drug development efforts that focused on single targets failed to provide effective treatment for Alzheimer’s disease (AD). Therefore, we designed cholinesterase inhibition (ChEI)-based multi-target-directed ligands (MTDLs) to simultaneously target AD-related receptors. We built a library of 70 compounds, sequentially screened for ChEI, and determined σ1R, σ2R, NMDAR-GluN2B binding affinities, and P2X7R antagonistic activities. Nine fulfilled in silico drug-likeness criteria and did not display toxicity in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 120 publications
1
18
0
Order By: Relevance
“…Analysis results of their molecular structures indicated that the modification of these two alkaloids could be exerted at multiple sites, which may probably improve their bioavailability and biological activity ( Shan et al, 2011 ; Yan B. et al, 2017 ; Liang et al, 2021 ; Castellano et al, 2022 ). Notably, the rational structural modifications of AChE inhibitors were still the primary route to the discovery of novel One-molecule-multi-target anti-AD drugs at this stage ( Rossi et al, 2021 ; Sang et al, 2022 ; Turgutalp et al, 2022 ). Since these two alkaloids’ high potential in vitro acetylcholinesterase inhibitory activity had been verified by other researchers ( Jia et al, 2021 ; Tang et al, 2021 ; Miao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis results of their molecular structures indicated that the modification of these two alkaloids could be exerted at multiple sites, which may probably improve their bioavailability and biological activity ( Shan et al, 2011 ; Yan B. et al, 2017 ; Liang et al, 2021 ; Castellano et al, 2022 ). Notably, the rational structural modifications of AChE inhibitors were still the primary route to the discovery of novel One-molecule-multi-target anti-AD drugs at this stage ( Rossi et al, 2021 ; Sang et al, 2022 ; Turgutalp et al, 2022 ). Since these two alkaloids’ high potential in vitro acetylcholinesterase inhibitory activity had been verified by other researchers ( Jia et al, 2021 ; Tang et al, 2021 ; Miao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the multifactorial nature of AD, a drug treatment approach that targets multiple causative agents (existing or yet-to-be-identified) simultaneously will be a rewarding route. We recently used our acute amyloidosis model in zebrafish to successfully evaluate potent cholinesterase (ChE) inhibition-based multitarget-directed ligands for their efficacy and mechanism of action on synaptic integrity . We designed a structural scaffold targeting AD-related receptors with ChE background inhibition that not only yields a symptomatic effect but also could provide DMT through neuroprotection.…”
mentioning
confidence: 91%
“…We performed extensive cytotoxicity screening and obtained few promising compounds that were tested for their in vitro cytoprotective efficacies. These studies displayed equal/better synaptic protection compared to benchmark drug donepezil in our zebrafish model of acute amyloidosis-induced synaptic degeneration . This in vivo study allowed us to increase the number of candidates for further drug discovery studies and provided a pipeline that could be successfully used to develop first-in-class drug candidates by performing a phenotypic screening of a drug library that targets key AD-related proteins (Figure ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously generated an adult AD zebrafish model and found that a complex set of cellular crosstalk leads to production of more neurons despite the disease ongoing pathology 912 . This model has strong parallelism to human AD brains in terms of molecular programs affected by AD pathology 13 , served as a pre-clinical tool for drug screening 1416 and helped identify genes associated with AD in humans 17,18 . The extraordinary regenerative ability of astroglia in zebrafish in AD-like scenarios rely on set of molecular mechanisms, one of which is the pro-neurogenic activity through the expression of nerve growth factor receptor ( ngfra ) 9,19 .…”
Section: Introductionmentioning
confidence: 99%